PERSAINGAN USAHA TIDAK SEHAT DI INDONESIA MENURUT HUKUM EKONOMI ISLAM DAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Is Susanto; Maya Meilia; Darania Anisa (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The growth of various business sectors in Indonesia has shown quite rapid development, both in the industrial and service sectors, so that in turn competition will emerge that should be seen as positive, where with the competition itself, business actors will compete to continue to improve their products or services generated so that businesses continue to innovate and strive to provide the best products or services for consumers. According to the results of research that business competition according to Islamic economic law is permissible competition, as long as business competition is carried out in a healthy manner, but if the business competition is monopolistic in order to take advantage, then the Islamic economy prohibits it. This is because Islamic economics provides a line that business competition must be conducted fairly (fair play) with the principles of honesty (honesty), openness (transparentcy), and justice (justice). Meanwhile according to Law No. 5 of 1999, business competition is permissible competition, however if competition between business actors in carrying out production and or marketing activities of goods and or services carried out in a manner that is dishonest or against the law or inhibits business competition, according to the provisions of Article 17 paragraph (1) Law No. 5 of 1999, such business competition is prohibited.